Clickable polyurethanes based on s- triazine ring containing aromatic diisocyanate bearing pendent alkyne group: synthesis and postmodification - Garg, Kavita; Chatterjee, Deepshikha; Wadgaonkar, Prakash (Journal of Polymer Science Part A Polymer Chemistry, 2017)
A new s-triazine ring containing aromatic diisocyanate bearing a pendent alkyne group, namely, 2,4-bis(4-isocyanatophenoxy)−6-(prop-2-yn-1-yloxy)−1,3,5-triazine was synthesized and reacted with various diols viz., 1,10-decanediol, tetraethylene glycol and polyethylene glycols in the presence of dibutyltin dilaurate as the catalyst to obtain a series of linear polyurethanes. The selected polyurethanes possessing pendent alkyne groups were postmodified with chemically diverse azides viz., 1-(azidomethyl)benzene, 1-(azidomethyl)pyrene, and methoxy end-caped poly(ethylene glycol) azide via copper-catalysed azide-alkyne Huisgen 1,3-dipolar cycloaddition. FTIR and 1H NMR spectra indicated quantitative click reaction. UV–vis and fluorescence spectroscopic analysis confirmed complete incorporation of pyrenyl groups indicating the formation of fluorescence active polyurethane by postmodification with 1-(azidomethyl)pyrene. TG analysis of polyurethanes indicated two stage weight loss and their thermal stability, as judged by T10 values, was governed by weight percent of urethane linkages. The water contact angle measurements revealed improved wettability with increased content of PEG either in the backbone of polyurethanes or as grafted chains. DLS and TEM studies confirmed that certain polyurethanes possessing PEG segments displayed self-assembly in aqueous solution, which was further supported by pyrene encapsulation studies using UV–vis spectroscopy. © 2017 Wiley Periodicals, Inc. J. Polym. Sci., Part A: Polym. Chem. 2017, 55, 1008–1020
Keywords: Click chemistry; Diisocynate; Polyethelene Glycol; polyurethanes; Self- Assembly